2017
DOI: 10.1515/geochr-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence of synthetic zircon implanted by He<sup>+</sup> ion

Abstract: He + ion implantation at 4.0 MeV, equivalent to energy of α particles from natural radioactive nuclei 238 U and 232 Th, has been conducted for undoped synthetic zircon. The cathodoluminescence (CL) of implanted samples was measured to clarify the radiation-induced effects. Unimplanted synthetic zircon shows pronounced and multiple blue emission bands between 310 nm and 380 nm, whereas the implanted samples have an intense yellow band at ~550 nm. The blue emission bands can be assigned to intrinsic defect cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Gaft [8] noted that in some natural zircons, annealing of radiation damage by heat treatment removed the broad and intense 570 nm component and revealed poorly understood blue and red spectral components that were tentatively attributed to defects related to Ti-O complexes and Ti 3+ and Fe 3+ , respectively (but see also [10]). Similarly, in a natural setting, the quenching of the yellow response due to increasing radiation damage-as has already been documented in synthetic samples for PL [5] and CL [11,32]-could increase the relative contribution of a weaker red component. In this way, variation from yellow to red in our PL images may indirectly reflect increasing radiation damage and U + Th concentration.…”
Section: Origins Of the Visible Pl Colormentioning
confidence: 64%
See 1 more Smart Citation
“…Gaft [8] noted that in some natural zircons, annealing of radiation damage by heat treatment removed the broad and intense 570 nm component and revealed poorly understood blue and red spectral components that were tentatively attributed to defects related to Ti-O complexes and Ti 3+ and Fe 3+ , respectively (but see also [10]). Similarly, in a natural setting, the quenching of the yellow response due to increasing radiation damage-as has already been documented in synthetic samples for PL [5] and CL [11,32]-could increase the relative contribution of a weaker red component. In this way, variation from yellow to red in our PL images may indirectly reflect increasing radiation damage and U + Th concentration.…”
Section: Origins Of the Visible Pl Colormentioning
confidence: 64%
“…Specifically, it was shown that yellow PL with a decay time of 30-35 µsec could be removed by heating to~700 • C and then be restored by neutron or alpha irradiation. This result has been confirmed by irradiation experiments on synthetic zircon samples [5,10,11]. In these experiments it was found that irradiation with alpha particles [5,10], neutrons [10], and oxygen ions [5] induced broadband yellow PL, while irradiation with X-rays and gamma radiation did not [10]-indicating that the broadband PL is related to the creation of point defects rather than irradiation-associated ionization [5,10].…”
Section: Introductionmentioning
confidence: 63%
“…The C3 is activated in the radiation‐induced metamictization (e.g., Finch et al, 2004; Gaft et al, 2005; Götze et al, 1999; Nasdala et al, 2002; Tsuchiya et al, 2017). The increase in the C3 intensity is attributed to the increased radiation dose (e.g., Nasdala et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The C1 is closely connected to structural bonds in a host lattice (e.g., Cesbron et al, 1995;Tsuchiya et al, 2015), indicating the intrinsic center peaks of ~310 and ~380 nm are due to Zr-O bond and O-O bond, respectively (Cesbron et al, 1995). Bond distortion and breakage in the crystal structure reduce the intensity of the C1 depending on the radiation damage according to Tsuchiya et al (2017). The degree of radiation damage depends on the concentration of radioactive elements such as U and Th in zircon and the time elapsed from the crystallization of zircon (e.g., Ewing et al, 2003;Finch et al, 2004;Zeug et al, 2018).…”
Section: Relationship Between CL Intensity and Crystallization Agementioning
confidence: 99%